2017
DOI: 10.1111/jphp.12679
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic analysis and chemical characterization of fractions of the hydroalcoholic extract of the Euterpe oleracea Mart. seed in the MCF-7 cell line

Abstract: In this study, we demonstrated that EAF was the most effective fraction in reducing cell viability and causing necroptosis in the MCF-7 cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…First, it was performed a chemical characterization of the extract and their fractions obtained with chloroform, ethyl acetate, and water to define the catechin-rich one to be used in the biological experiments. The phytochemical analysis showed that in the ethyl acetate fraction, mainly catechins and pelargonidin were identified, which differ from the previous results of our laboratory, in which a predominance of proanthocyanidin A2, trimeric and tetrameric procyanidins was observed [ 30 ]. Other studies also describe the occurrence of catechins and epicatechin in the açaí seed [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…First, it was performed a chemical characterization of the extract and their fractions obtained with chloroform, ethyl acetate, and water to define the catechin-rich one to be used in the biological experiments. The phytochemical analysis showed that in the ethyl acetate fraction, mainly catechins and pelargonidin were identified, which differ from the previous results of our laboratory, in which a predominance of proanthocyanidin A2, trimeric and tetrameric procyanidins was observed [ 30 ]. Other studies also describe the occurrence of catechins and epicatechin in the açaí seed [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previously, our group described the antitumorigenic action of açaí in a breast cancer cell line (MCF-7) due to açaí promoting a significant reduction in cell viability, changing cell morphological characteristics and inducing autophagy [ 26 ]. Corroborating this result, Freitas and colleagues [ 37 ] also recently revealed that açaí reduced cell viability of MCF-7 cell. However, these authors showed that the ethyl acetate fraction (EAF) is the most cytotoxic part of the hydroalcoholic extract of açaí seed and induced cell necrosis in the MCF-7 cells [ 37 ].…”
Section: Discussionmentioning
confidence: 67%
“…Corroborating this result, Freitas and colleagues [ 37 ] also recently revealed that açaí reduced cell viability of MCF-7 cell. However, these authors showed that the ethyl acetate fraction (EAF) is the most cytotoxic part of the hydroalcoholic extract of açaí seed and induced cell necrosis in the MCF-7 cells [ 37 ]. So, to our knowledge, this report is the first study to evaluate the effects of açaí against DMBA-induced mammary carcinogenesis in a rat model.…”
Section: Discussionmentioning
confidence: 67%
“…A total of 60 publications were identified in the databases; however, 31 were duplicate articles. Among the 29 articles selected, 20 were excluded based on the titles and abstracts because they did not meet the inclusion criteria: 2 were literature reviews [ 7 , 24 ]; 6 did not study açaí in an animal model of cancer and/or did not perform a toxicological analysis [ 25 30 ]; 10 were in vitro studies [ 13 , 20 , 31 38 ]; and 2 did not use the order Rodentia [ 21 , 39 ]. After reading the full texts 9 articles were included for their critical evaluations of the safety and effectiveness of açaí in animal experimental models [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the ability of açaí to inhibit carcinogenesis, and the incidence and multiplicity of tumors in experimental models of cancer using rodents, in vitro studies also showed that açaí decreased cell viability, suppressed proliferation and induced apoptosis, suggesting the anticancer and antioxidant activity of açaí against C-6 rat brain glioma cells [ 49 ], MCF-7 breast cancer cells [ 13 , 38 ] and colon cancer cells [ 34 ]. These results suggest that açaí contains phytochemicals that can be used as natural chemopreventive agents [ 13 , 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%